2021
DOI: 10.3390/ijms22041732
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Low-Grade Chronic Inflammation and Intrauterine Programming of Health and Disease

Abstract: Overweight and obesity during pregnancy have been associated with increased birth weight, childhood obesity, and noncommunicable diseases in the offspring, leading to a vicious transgenerational perpetuating of metabolic derangements. Key components in intrauterine developmental programming still remain to be identified. Obesity involves chronic low-grade systemic inflammation that, in addition to physiological adaptations to pregnancy, may potentially expand to the placental interface and lead to intrauterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 136 publications
2
42
0
Order By: Relevance
“…Alternately, induction of preterm birth by mid-pregnancy administration of heat-killed E. coli resulted in significantly increased levels of IL-1α, IL-1β, and IL-6 in the uterus, while TNF-α levels were similar to controls [62]. Additionally, low-grade inflammation in the placenta, as observed with low doses of HSV-2 in our study, has been observed in pregnancies complicated by maternal obesity that result in adverse pregnancy outcomes, including congenital abnormalities and fetal macrosomia, in the absence of more severe outcomes [63,64]. Further, in a study conducted using first trimester placental tissues obtained from normal pregnancies and spontaneous abortions, only placental tissues from spontaneous abortions were associated with unstimulated production of inflammatory mediators [65].…”
Section: Discussionsupporting
confidence: 58%
“…Alternately, induction of preterm birth by mid-pregnancy administration of heat-killed E. coli resulted in significantly increased levels of IL-1α, IL-1β, and IL-6 in the uterus, while TNF-α levels were similar to controls [62]. Additionally, low-grade inflammation in the placenta, as observed with low doses of HSV-2 in our study, has been observed in pregnancies complicated by maternal obesity that result in adverse pregnancy outcomes, including congenital abnormalities and fetal macrosomia, in the absence of more severe outcomes [63,64]. Further, in a study conducted using first trimester placental tissues obtained from normal pregnancies and spontaneous abortions, only placental tissues from spontaneous abortions were associated with unstimulated production of inflammatory mediators [65].…”
Section: Discussionsupporting
confidence: 58%
“…More specifically, a higher adherence to the MD was associated with the prevention of GDM (26,27) , decreasing the risk of compromised fetal growth, prematurity, neural tube defects, asthma, allergy as well as a decrease in the cardio-metabolic risks for both mother and child (28,29) . Pregnancy has been considered as a physiological low-grade systemic inflammatory status with the placenta producing a range of inflammatory cytokines (30) . The protective effect of the MD against metabolic abnormalities during pregnancy could be due to the fact that this pattern is rich in antioxidants nutrients (vegetables and fruits) or antioxidant phenols (olive oil and red wine).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity plays a pivotal role in the pathogenesis of inflammaging, since the massive expansion of the adipose tissue, as a highly active endocrine organ, affects immune cell profile, deranges inflammatory cytokines production, and finally impairs metabolic function [11]. Such a metabolic dependent pro inflammatory background, the so-called meta-inflammation, in turn, influences the metabolism itself leading to increased oxidative stress and insulin resistance [12].…”
Section: Obesitymentioning
confidence: 99%
“…Once pregnancy is established, the modulation of the maternal immune system is crucial to the embryo development and pregnancy maintenance [68]. Despite the historical idea that maternal systemic immune suppression is essential for fetal acceptance, a more complex feto-maternal immune interaction has been recently described, with both intrauterine and systemic inflammation as pivotal components of healthy pregnancies [11]. In this scenario, several pregestational maternal stressors (i.e., obesity, chronic comorbidities, advanced maternal age, malnutrition, smoking) have been associated with maladaptive changes in pregnancy and obstetric complications with disrupted intrauterine environment and fetal development.…”
Section: Effects Of Inflammaging On Pregnancy Outcomes and Fetal Prog...mentioning
confidence: 99%